Elevated 18:0 lysophosphatidylcholine contributes to the development of pain in tissue injury. Issue 2 (7th June 2022) - Friston, Dominic Anthony; Cuddihy, Joshua; Souza Luiz, Jessica; Truong, An Hoai; Ho, Laptin; Basra, Meirvaan; Santha, Peter; Oszlacs, Orsolya; de Sousa Valente, Joao; Marczylo, Tim; Junttila, Sini; Laycock, Helen; et al.
Abstract : Supplemental Digital Content is Available in the Text. 18:0 lysophosphatidylcholine exhibits up-regulation in burn tissues and, through modifying the lateral pressure in primary sensory neurons, contributes to pain in burn injury. Abstract: Tissue injuries, including burns, are major causes of death and morbidity worldwide. These injuries result in the release of intracellular molecules and subsequent inflammatory reactions, changing the tissues' chemical milieu and leading to the development of persistent pain through activating pain-sensing primary sensory neurons. However, the majority of pain-inducing agents in injured tissues are unknown. Here, we report that, amongst other important metabolite changes, lysophosphatidylcholines (LPCs) including 18:0 LPC exhibit significant and consistent local burn injury-induced changes in concentration. 18:0 LPC induces immediate pain and the development of hypersensitivities to mechanical and heat stimuli through molecules including the transient receptor potential ion channel, vanilloid subfamily, member 1, and member 2 at least partly via increasing lateral pressure in the membrane. As levels of LPCs including 18:0 LPC increase in other tissue injuries, our data reveal a novel role for these lipids in injury-associated pain. These findings have high potential to improve patient care.